The invisibility of ruling texts: An institutional ethnographic scoping review of family caregivers’ information work - Dalmer, Nicole K. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2018)
To make visible how different facets of family caregivers’ eldercare work are highlighted or obscured in academic writing and research, this institutional ethnography-based scoping review examined the conceptualizations and portrayals of family caregivers’ information work in scholarship and the degree to which this type of work is recognized. In doing so, this study deepens our understanding of the complex relationship between information and care by exploring how texts come to regulate our understanding about and research surrounding information-related care work.